PENGARUH KONSUMSI JANTUNG PISANG TERHADAP PRODUKSI ASI PADA IBU NIFAS - Ulva Noviana (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2019)
Exclusive breastfeeding production is the resultof breast stimulation by the prolactin hormoneproduced by the anterior pituitary gland. If the babysucks, the Exclusive breastfeeding will be removedfrom the lactiferous sinuses. The purpose of thisstudy is to analyze differences on Exclusivebreastfeeding production after consuming thebanana infloresence. The design used in this study is one grouppretest posttest design, independent variable isbanana infloresence and the dependent variable isthe production of exclusive breastfeeding. Population in study were all postpartum motherswho breastfeed on the first child (primi gravidarum)in Gertenga village POSKESDES Septian Eka KST,r.keb Karang penang subdistrict Sampang asmuch as 10, a sample of 10 respondents, takingsample technique uses simple random sampling.Data retrieval uses questionnaire sheet and a pairedSample test Rank statistical test with α (0.05). The results showed that all of them (100%)suffered from non-smooth breastfeeding preoductionbefore being given banana infloresence drink andafter being given banana infloresence drink almostall (80%) breast milk was smooth. Based on thestatistical test paired Sample test Rank test resultsobtained p value (0.002) <α (0.05) then Ha isaccepted and H0 is rejected which means that there is a difference in exclusive breastfeeding production after consuming the banana infloresence. Suggestionfor postpartum mothers who are breastfeeding whohave not smooth exclusive breastfeeding productionis to start getting used to consuming food or drinksthat can facilitate the production of breastfeeding,one of them is the banana infloresence drink